Automated Deduction - CADE 29 29th International Conference on Automated Deduction, Rome, Italy, July 1-4, 2023, Proceedings - Pientka, Brigitte; Tinelli, Cesare (Lecture Notes in Artificial Intelligence,, 2023)
This open access book constitutes the proceedings of the 29th International Conference on Automated Deduction, CADE 29, which took place in Rome, Italy, during July 2023. .